The Controversies of Hardline Islam In Indonesia: A Conflict Resolution Approach - Nurkhalis; Marhaban (Islam Transformatif : Journal of Islamic Studies, 2024)
The existence of hardline Islam in Indonesia has changed the shocking Islamic culture without violence and has presented an attitude of extreme and radical actions. This research is studied through a qualitative approach with library research. The purpose of this research is to suggest Indonesian hardliner Islam and the government respond to every hardliner maneuver not equated with handling terrorists with a pattern of shot to kill. Therefore, the problem-solving of Indonesian hardliner Islam is resolved by Galtung-style conflict resolution with a “positive peace” step. The results of the research reveal that Indonesian hardline Islam cannot be equated with hardline Islamic movements in other Muslim countries that are similar to the Taliban style or terrorist movements. Most Indonesian hardline Islam is treason, extortion, and undermining against Pancasila by imposing the value of sharia as an effort in “shariatization” so that their movements contradict the highest state regulations that they fall into actions in the criminal category. Keberadaan Islam garis keras di Indonesia telah mengubah budaya Islam yang mengejutkan tanpa kekerasan menjadi sikap yang ekstrim dan radikal. Penelitian ini dikaji melalui pendekatan kualitatif dengan jenis penelitian kepustakaan. Tujuan dari penelitian ini adalah untuk memberikan saran kepada Islam garis keras Indonesia dan pemerintah untuk menyikapi setiap manuver kelompok garis keras tidak disamakan dengan penanganan teroris dengan pola diintai kemudian tembak mati. Oleh karena itu, penyelesaian masalah Islam garis keras Indonesia diselesaikan dengan resolusi konflik ala Galtung dengan langkah “perdamaian positif”. Hasil penelitian mengungkapkan bahwa Islam garis keras Indonesia tidak bisa disamakan dengan gerakan Islam garis keras di negara-negara Muslim lainnya yang mirip dengan gaya Taliban atau gerakan teroris. Sebagian besar Islam garis keras Indonesia bersifat makar dan merusak pemahaman terhadap Pancasila dengan memaksakan nilai syariatisasi sehingga gerakan mereka bertentangan dengan peraturan tertinggi negara sehingga masuk ke dalam tindakan yang dapat diklasifikasikan dalam kategori kriminal.